The Impact of Nagari Expansion on Administrative Services for Javanese Transmigrant Communities in Nagari Lingkuang Aua, Pasaman District, West Pasaman Regency - Sutanto, Satrio Hadi; Putri, Nora Eka (The Future of Education Journal, 2026)
Nagari division is a local government policy aimed at improving the effectiveness of governance and accelerating public services to the community. However, in practice, regional division policies can also create various administrative problems at the community level. This condition occurred in Javanese transmigrant communities in Jorong Simpang Empat Kaplingan, which experienced changes in administrative areas following nagari division. This study aims to describe the impact of nagari division on administrative services for Javanese transmigrant communities in Jorong Simpang Empat Kaplingan and to identify various obstacles that arose in the administrative service process. This study uses a descriptive qualitative approach with data collection through interviews, observation, and documentation. Research informants consisted of nagari officials, nagari division teams, and the community of Jorong Simpang Empat Kaplingan. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results show that nagari division has a positive impact in the form of increased development focus and more targeted services. However, the division also has negative impacts, including changes in population administrative data without adequate socialization, delays in social assistance distribution, and confusion among Javanese transmigrants regarding the existence of the Nagari Customary Council. Therefore, improved policy socialization and better coordination between nagari government and the community are needed.